1984
DOI: 10.1111/j.1469-8137.1984.tb03605.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF MYCORRHIZAL INFECTION OF GOODYERA REPENS AND ITS CONTROL BY FUNGICIDE

Abstract: Summary Studies of the orchid Goodyera repens Br. growing on agar media in association with its natural endophyte Rkizoctonia goodyerae‐repentis Constantin and Dufour showed that mycorrhizal plants of different developmental stages had significantly higher growth rates and level of P and N than did uninfected ones. Treatment of mycorrhizal plants with the fungicide thiabendazole stopped growth of external mycelium and caused a significant decrease in growth rate, P and N content, percentage infection and net a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Studies of G. repens indicated a marginal importance of mycotrophy in that species (Alexander & Hadley, 1984, 1985), although the level of infection was high (up to 40–80%) in both roots and rhizome (Alexander & Alexander, 1984). In contrast to its relative, in G. pubescens infection was restricted to the proximal parts of roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of G. repens indicated a marginal importance of mycotrophy in that species (Alexander & Hadley, 1984, 1985), although the level of infection was high (up to 40–80%) in both roots and rhizome (Alexander & Alexander, 1984). In contrast to its relative, in G. pubescens infection was restricted to the proximal parts of roots.…”
Section: Discussionmentioning
confidence: 99%
“…In species that do develop green leaves, the adult stages are often assumed to be entirely phototrophic, but little is known about transition from the mycotrophic seedling stage. The study by Alexander and Hadley (1984, 1985) seems to show a transition in Goodyera repens from entirely mycotrophic seedlings to leafy young plants that could grow despite fungicide treatment. However, it seems likely that in some species mycotrophy persists and supplements photosynthesis for the entire life history.…”
Section: Introductionmentioning
confidence: 94%
“…However, no such effect was seen when the fungicides were applied to detached L. rupestris leaves (data not shown). No cytokinin-like effects were reported in previous studies that used fungicides (including benomyl and propiconazole) to obtain fungusfree plants (Alexander & Hadley 1984;Reisen & Close 1987;Fitter & Nichols 1988;see Paul et al 1989). This is the first study to test the importance of fungi for growth and survival of epiphytic orchids in the field.…”
Section:        mentioning
confidence: 94%
“…As the biology of orchid mycorrhizal fungi is still a mystery (Otero et al 2002), the most practical way to study this problem in the field is by eliminating mycorrhizal fungi with fungicides. This has been done for the terrestrial orchid Goodyera repens (Alexander & Hadley 1984) and for other plants (Riesen & Close 1987;Fitter & Nichols 1988;Carey et al 1992), but has not been reported previously for epiphytic orchids.…”
Section:        mentioning
confidence: 99%
“…The fungi also help turn plant cellulose into carbohydrates that are easily absorbed, and can act as a carbon source for orchids (Smith, 1966). Furthermore, OMF provides minerals, vitamins, and other nutrients for plants (Bernard, 1911;Hadley, 1984;Alexander and Hadley, 1985), promotes the absorption of nitrogen, phosphorus and potassium for seedlings (Alexander and Hadley, 1984;Zhao et al, 1999), and promotes plant growth and development, which finally leads to better reproduc-tive growth than in NM control plants. These results lead to the conclusion that the symbiotic relationship between OMF and P. tankervilleae enhances the photosynthetic rate, seedling viability, and repro-duction growth.…”
Section: Resultsmentioning
confidence: 99%